Credit Systems for Bycatch and Biodiversity Conservation - Squires, Dale; Lent, Rebecca; Dutton, Peter H.; Dagorn, Laurent; Ballance, Lisa T. (Frontiers in Marine Science, 2021)
Credit systems for bycatch mitigation, an incentive-based approach, change vessel behavior and decision-making and allow vessels to flexibly reduce bycatch in a vessel’s own, least-cost way. There are two types of credit systems, both originally developed to manage environmental pollution. The first evolved out of direct regulation by limits made flexible through the creation of unused limits – credits – with the option to compensate the excess use of one source by excess control of another internal or external source. The second is a penalty-reward system that incentivizes bycatch-reducing vessel behavior through rewards and penalties in either cash or kind for positive and negative behavior, respectively. Two case studies are considered, Scottish Conservation Scheme and halibut bycatch reduction in the Alaskan multispecies groundfish fishery. Bycatch conservation is addressed through the biodiversity mitigation hierarchy.